PELATIHAN MEMBANGUN KREATIVITAS DAN LITERASI KEUANGAN BAGI GENERASI MILENIAL - Sukma Irdiana; Kusnanto Darmawan; Kurniawan Yunus Ariyono (LPPM Universitas Bina Bangsa, 2023)
Community service activities are part of the Tridharma of higher education that must be carried out. Financial literacy is defined as a person's knowledge and ability to manage finances. The millennial generation or the generation that is currently aged 20-30 years is the generation that sucks the most in managing finances. This is because the millennial generation has a different lifestyle from the previous generation. The purpose of this activity is to increase financial literacy for the millennial generation. Then to increase the creativity of the millennial generation in financial literacy, the PkM Team of the Widya Gama Lumajang Institute of Technology and Business carried out activities through several stages, reviewing the location of activities, applying for activity permits, preparing activities, to the implementation of activities. The results of this activity are expected to increase financial literacy for the millennial generation in Pasrujambe District. The presence of innovative goods from the creativity of the millennial generation, as well as useful activities as an effort to unite two generations of different eras